Tribological Tests Effect on Changes in the Surface Layers of Iron-Containing Antifrictional Aluminum Alloys - Mezrin, Aleksey M.; Shcherbakova, Olga O.; Muravyeva, Tamara I.; Zagorskiy, Dmitry L.; Shkalei, Ivan V. (Frontiers in Mechanical Engineering, 2019)
Antifrictional properties and surface parameters of Al-Si-Cu-Sn-Pb alloys have been investigated. The effect of iron addition (approx. 1 %) on the structure and tribological properties of aluminum alloy samples has been studied. Tribological properties were explored using the “shoe-roller” scheme with step-by-step pressure changes. The investigations were carried out both in and without a lubricant. The SEM- (with elemental analysis) and SPM-microscopy methods were applied to study sample surface and under-surface layers of the samples at the transversal sections. After tribological tests have been carried out, the topography of both surface and under-surface layers at the transversal sections has been studied. During the tests without lubrication solid particles, presumably, oxides, were formed. The particles increase the surface destruction, thus, doing their part of an abrasive and contributing to (scuffing) score. After testing in the lubricant particles containing silicon and copper and having a rounded shape were also formed. These particles remain on the surface and are rolled in the lubricant. They creating a kind of a "protective cover" contributing to the contact pair stable operation. The under-surface layer 50-100 micrometers thick formation was found at the sections after tribological tests without lubrication. The samples sections were prepared after testing with lubrication. The study of the samples sections demonstrated the formation of the under-surface layer with thickness 30-40 micrometers. The elements redistribution in these layers was shown. After the tribological tests were carried out, the counterbodies (rollers) were also explored. The SPM method has been shown the film formed on the surface is uneven in thickness after tests without lubrication. This leads to the macrorelief development during friction and can lead to (scuffing) score. On the contrary, after tests in lubricant the secondary structures film formed is distributed on the surface as a thin uniform layer. This film has the protective properties. It was shown that alloys containing iron (up to 1%) have good tribological characteristics when tested both in and without the lubricant. Thus, they can be used as antifrictional materials.